Rodinný dům v Těšeticích - Krahulcová, Šárka (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Bakalářská práce řeší návrh rodinného domu. Rodinný dům se bude nacházet v obci Těšetice, v katastrálním území „Těšetice u Olomouce“. Dům je samostatně stojící, je navržen pro čtyřčlennou rodinu. Objekt má dvě podlaží a není podsklepen. Hlavním konstrukčním systémem je zdivo z pórobetonových tvárnic Ytong, zateplené minerální izolací z kamenných vláken. Objekt je části zastřešen pultovou střechou se sklonem 5°, z části plochou střechou.

The Bachelor´s thesis solves a design of the family house. The family house will be in village called Těšetice, in the cadastral municipality "Těšetice u Olomouce". The house id independently standing, it is designed as house for a family of four. The building has two floors and the building has no basement. The main construction system are walls constructed from Ytong porous concrete blocks, insulated by mineral insulation from stone-made fibers. The building is partly covered by shed roof with gradiet 5°and partly is covered by flat roof.
Family house, Těšetice
Keywords: Rodinný dům; podlaží; nepodsklepený; střecha; pultová střecha; plochá střecha; zdivo; zateplení; konstrukční detaily; Family house; floor; no basement; roof; shed roof; flat roof; masonry; insulation; construction details